Safety, Immunogenicity and Antibody Persistence of Rift Valley Fever Virus Clone 13 Vaccine in Sheep, Goats and Cattle in Tanzania - Sindato, Calvin; Karimuribo, Esron D.; Swai, Emmanuel S.; Mboera, Leonard E. G.; Rweyemamu, Mark M.; Paweska, Janusz T.; Salt, Jeremy (Frontiers in Veterinary Science, 2021)
Background: Vaccination remains the best approach to control Rift Valley fever (RVF) in animals and consequently in humans. This study assessed the efficacy and safety of RVF virus (RVFV) Clone 13 vaccine under field conditions. Methodology: A vaccine trial was conducted in sheep (230), goats (230), and cattle (140) in Ngorongoro district, Tanzania. Half of each of the animal species were vaccinated and the other half received the placebo. Animals were clinically monitored and bled before vaccination and at days 15, 30, 60, 180 and 360 (+/- 10) post-vaccination to measure antibody responses to RVFV. Survival analysis was conducted to measure time until antibody production had occurred and to compare the cumulative proportion of antibody production over time. Results: Of 600 animals included in the study, 120 animals were lost during the study, leaving a total of 480 (243 in the vaccinated group and 237 in the control group) for complete follow-up. There was no adverse reaction reported at the injection site of the vaccine/placebo in all animals. Abortions, deaths, or body temperature variations were not associated with vaccination (p>0.05). By day 15 post-inoculation, IgG seroconversion in vaccinated goats, cattle and sheep was 27.0% (n=115), 20.0% (n=70) and 10.4% (n=115), respectively. By day 30 post-inoculation, it was 75.0% (n=113), 74.1% (n=112) and 57.1% (n=70) in vaccinated sheep, goats and cattle, respectively. By day 60 it was 88.1% (n= 109), 84.3% (n=108) and 64.60% (n=65) in sheep, goats and cattle, respectively. By day 180, it was 88.0% (n= 108), 83.8% (n=105) and 66.1% (n=62) in sheep, goats and cattle, respectively. By day 360, it was 87.2% (n=94), 85.6% (n=90) and 66.1% (n=59) in sheep, goats and cattle, respectively. Conclusion: RVFV Clone 13 vaccine is considered safe, with high immunogenicity in sheep and goats and moderate in cattle. It induced detectable, but variable levels of IgG responses.